Steroscopic discrimination in infants. - Atkinson, J; Braddick, O (1976)
The ability to make discrimiations of binocular disparity was investigated in 2-month-old infnats by two methods: (a)fixation preference between patterns differing in the disparity they contained, and (b)recovery from habituation of high-amplitude sucking when there was a change in disparity in the visual reinforcer. The stimuli were random-dot steregrams. The results for both mthods indicated that at least some infants of this age could perform steroscopic discriminations and that both techniques were feasible for development for longitudinal studies of steroscopic vision.